Peran dari Integrated Marketing Communication terhadap Brand Equity - Kandhogo, Ari Titis Bimo (Interaksi: Jurnal Ilmu Komunikasi, 2014)
Brand equity is an intangible aset but has a very important role for a company. Eventhough intangible, but brand equity has same important role with another company aset. To build and develop brand equity, company needs to create an unique, identic and favorable brand association. Integrated Marketing Communication considered as an exact concept for company to communicate with the consument and stakeholder. Good communication between company, consument and stakeholder will give a positive impact for brand equity. This paper will analyzes the role of Integrated Marketing Communication and the effect to the brand equity, also the role of brand equity for a company.